Risk Analysis of Sequential Dam Break of Cascade Reservoirs and Simulation of Flood Routing - YU Zibo; XIANG Yan; MENG Ying; SU Zhengyang (Renmin Zhujiang)
To study the risk of sequential dam break of cascade reservoirs,and to simulate and analyze the flood routing process,by constructing a Bayesian network model for the sequential dam break of double reservoirs under the action of extra standard floods and piping,and combining the dam break and flood routing simulation of Breach dam-break numerical model and two-dimensional HEC-RAS hydrodynamic model,this paper calculates the probability of dam break,evaluates the risk of sequential dam break,and simulates the flood routing process,taking Hanconggou Reservoir and Dingguoshan Reservoir as examples.The calculation results show that:Through Bayesian-based backward inference of the known dam break of Dingguoshan Reservoir,the probability of “Hancongou Reservoir dam break” increased from 3% to 87%;while through Bayesian-based backward inference of the known dam break of Hancongou Reservoir,the probability of “Hancongou Reservoir piping” increased from 16% to 87%.Under extra standard flood and piping conditions,due to the sequential dam break of the two reservoirs,the time for the flood to reach the section CS1—CS6 is 0.8~3.0 h;under the flood conditions that occurred once in 1 000 years,the Hancongou Reservoir was opened for flood discharge but the dam was not broken.Only the Dingguoshan Reservoir was over-topped with dam break,and the flood reached the section CS1—CS6 in 21.5~26.5 h.This study can provide scientific reference for reducing dam break risk,and making emergency plan and disaster prevention & mitigation plan.